Understanding Hadith On Social Ethics Among Generation Z:: A Living Hadith Study - Luhuringbudi, Teguh; Kuliyatun, Kuliyatun; Abdiguno, Panggih (Jurnal Man-anaa, 2025)
This study focuses on the understanding of hadith on social ethics among generation Z, adopting a living hadith approach. The main objective of this study is to identify how the teachings of hadith are applied in daily social interactions, including on social media. The data collection method was carried out through a questionnaire distributed online, while data analysis used a combination of qualitative and quantitative approaches. Primary sources consisted of relevant hadiths that were used as references by respondents in developing morality. The results indicate that the majority of respondents recognise the significance of honesty and politeness, with 72.8% incorporating these principles into their social interactions.The study's novel contribution lies in its exploration of generation Z's distinctive integration of religious teachings with intricate social realities.The study's limitations include its restricted scope and reliance on quantitative data, necessitating further research to develop a more in-depth qualitative approach. The study opens up new opportunities in discussions about the application of religious ethics in a modern context, which can provide implications for moral education among adolescents.